2019
DOI: 10.1177/1075547019862554
|View full text |Cite
|
Sign up to set email alerts
|

Routine Influences on Aquaculture News Selection: A Q Method Study With New England Journalists

Abstract: Environmental journalists, as gatekeepers, often become arbiters of risk and benefit information. This study explores how their routine news value judgments may influence reporting on marine aquaculture, a growing domestic industry with complex social and ecological impacts. We interviewed New England newspaper journalists using Q methodology, a qualitative dominant mixed-method approach to study shared subjectivity in small samples. Results revealed four distinct reporting perspectives—“state structuralist,” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It is found that analyzed news in this study have generally positive tone (n=309, 53,74%) about the sector. It is seen that aquaculture sector has been portrayed in media as negatively in most countries (Amberg & Hall, 2008;Schlag, 2011;Forechlich, Gentry, Rust, Grimm, & Halpern, 2017;Olsen & Osmundsen, 2017;Duffy, Rickard, & Grosswiler, 2019). In the case of this, when it is compared to the other studies, this result differs from studies in literature on this issue except Feucht and Zander (2016).…”
Section: Discussionmentioning
confidence: 72%
“…It is found that analyzed news in this study have generally positive tone (n=309, 53,74%) about the sector. It is seen that aquaculture sector has been portrayed in media as negatively in most countries (Amberg & Hall, 2008;Schlag, 2011;Forechlich, Gentry, Rust, Grimm, & Halpern, 2017;Olsen & Osmundsen, 2017;Duffy, Rickard, & Grosswiler, 2019). In the case of this, when it is compared to the other studies, this result differs from studies in literature on this issue except Feucht and Zander (2016).…”
Section: Discussionmentioning
confidence: 72%